Upaya Perlindungan Hukum terhadap Nasabah Perbankan melalui Prinsip Kerahasiaan Bank dalam UU No 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan - Nayla Azarine; Tesalonika David; Valsifa Utami (Pajak dan Manajemen Keuangan, 2024)
This paper discusses the principle of bank secrecy as an important instrument in legal protection for customers, as well as its relevance in maintaining public trust in the banking sector in Indonesia. Based on the legal framework stipulated in Law Number 10 of 1998 concerning Banking and Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK), this study highlights the obligation of banks to protect customer data, including exceptional situations regulated by law. Normative legal research is used to analyze legal principles, laws and regulations, and related literature. The principle of bank secrecy is considered a pillar of customer trust and the main capital in the financial ecosystem. However, challenges arise when this principle conflicts with the interests of law enforcement, such as criminal investigations. The regulations strengthened by the PPSK Law provide a foundation for customer data protection while also regulating administrative and criminal sanctions for violations. On the other hand, the application of this principle also contributes to financial stability by increasing literacy and compliance with regulations. This paper recommends harmonization between the protection of customer privacy rights and the effectiveness of law enforcement to maintain the sustainability of trust in the banking sector.